Spatial variation of the characteristics of the population married to more than one wife in Al-Muthanna Governorate for the year 2021 (Journal of Libya for geographical studies, 2022)
The research examines the demographic characteristics of more than one married woman in Muthanna governorate. It examines the demographic characteristics of the age composition of the married population with more than one wife, as well as the educational composition of this population, as well as the study of their occupational composition.The research aims to track the state of spatial disparity between the administrative units of the study area since 12 departmental and cross-district administrative units have been addressed, and in order to achieve the research objective relied on different office sources, including field study. (1058) Questionnaire form (Annex 1) according to the number of families in the study area for 2021 (105,712) by 1% and by number of households per administrative unit, as well as official and office sourcesThe research showed important results related to population characteristics, perhaps most notably: The number of married couples was more than 218 out of 1,058 questionnaires and up to (20.6%) of the total married in the area of study, and at the level of population characteristics is observed to exceed the age group (25-34 years) ranked first (41.3%) of the total number of married couples by more than one wife, a high proportion compared to other age groups, as well as urban-rural disparities and administrative units, and the research found that the proportion of married couples by more than one illiterate wife is higher than the rest of their educational levels. (22%) of the total total, as well as the significant relative variation between the administrative units of the school area, it is also noted that the proportion of married persons with more than one wife for the peasant profession is (28.9%) As it comes in first place of the total number of married couples by more than one wife and varies it locally at the level of administrative units of the school area.
Keywords: spatial disparity; marriage; Al-Muthanna Governorate